Is agricultural adaptation to global change in lower-income countries on track to meet the future food production challenge? - Thornton, Philip K.; Kristjanson, Patricia M.; Förch, Wiebke; Barahona, Carlos; Cramer, Laura K.; Pradhan, Sonali (Elsevier, 2018)
Agriculture is critical to sustainable development, and agricultural production by smallholders in lower-income countries contributes substantially to the food security of both rural and urban populations. Smallholders face many challenges related to urbanisation, sustainable use of natural resources and climate change. While there will be different ways of achieving sustainable agricultural systems, all will involve adaptation on a massive scale to meet the future food production challenge at greatly reduced carbon cost. Here we evaluate recent progress in agricultural adaptation using surveys in five regions, 21 countries and 45 sites, covering 315 villages and approximately 6300 households. These surveys include information about the changes made to farming systems in the last decade. We synthesise this information by grouping households into types: food insecure, hanging in, stepping up and stepping out. We then profile each site in terms of its proportion of households of these four types. While farmers have made some changes in their farming practices over the last decade, most changes have been incremental and piecemeal. We find little evidence in the study sites in any region of farming changes at the scale needed to enhance food security of significant proportions of the population. Searching for commonalities in the enabling environment among sites with similar proportions of household types, we found collective action at the community level coupled with appropriate climate information provision and the active participation of local organisations to be associated with higher levels of food security. To foster the changes needed in agricultural and food systems, a much stronger focus will be required on the enabling environment if food security goals are to be attainable. Without more nuanced and effective targeting of technological as well as institutional interventions, agricultural adaptation to meet the food production challenge in the coming decades is unlikely to occur.